Impactos emocionais causados pela mudança de estilo de gestão em um hospital na cidade de São Luis-MA - Bertulucci, Célia Regina (2006)
The objective of this study is to identify how a health institution can minimize the emotional impacts caused by the change of a style of classic management for a participative administration, that the workers and controllers can see the institution as a dynamic organization, that must be faced as an alive system, mobile and adaptable, where they is beings that have the right to react and to answer to the stimulatons. For that, the institution can handle motivator¿s instruments that develop in the people the potential to react of adequate way to the changes proposals, as well as increasing the perspective of possible technological improvements and interpersonal relationship between the internal and external customers. To change the style to manage, to hear the staff of support and user, are not part of the routine of the heads that develop classic management. This decision demands adaptation and flexibility, study, update and psychological preparation, to face common feelings to the new. It fits to the new directors, to visualize these feelings and work to minimize, avoiding future upheavals and the confrontation of situations that can harm the production of the company, as well as the quality of the communication between the diverse dimensions of the organization people. In this study case, based in phenomenological methodology, was possible to verify, through half-open interviews and comments, how was faced the feelings caused at the old direction time, composed for military who withheld the power and determined the actions of the hospital in study, was replaced by health professionals, that saw in the work team the best option to solve the problems and the potential to carry through an administration based in adequate strategies the reality of the moment, with the objective of reaching the satisfaction of the customer. Through this work, is possible to prove the theory that the changes cause impacts that affect the behavior of the people involved and cause stress, as well as conclude that despite the new direction show themselves, during the change, much made use to make right and involve all the workers, didn¿t have traced strategies to minimize the emotional impacts caused by the changes, what made all face their feelings of doubts and anxiety without no special care. Many obtained, by themselves, to face and to adapt the new proposals, but some could not assimilate the new administrative methodology and had been moved away definitively from the institution.